A geographic information system and analytic hierarchy process drought risk analysis approach in arid south-western Zimbabwe: Prospects for informed resilience building - Oshneck Mupepi; Mark Makomborero Matsa; John Hove (Nature-Based Solutions)
Climate change is increasing the vulnerability of communities to drought, with rural communities in developing countries being affected the most. The study assessed drought vulnerability in south western Zimbabwe based on the Analytic Hierarchy Process (AHP) supported by Geographic Information System (GIS) and remote sensing techniques. An empirical research design based on verifiable evidence of drought vulnerability was adopted. GIS and remote sensing data were used to execute the multi-criteria AHP for the determination of drought vulnerability. ArcMap 10.8 software was used for the analysis of drought influencing factors and carrying out the weighted overlay. Results indicate that almost the whole of south western Zimbabwe is prone to droughts with only 0.6 % of the area being comparatively better. It was also noted that the majority of the population are exposed to high and extreme risk of droughts as they are settled in extreme and high drought risk zones. The study recommends implementation of resilience building interventions from an informed dimension where specific resilience building initiatives are implemented in appropriate environments for high returns. This can sustain the communities in the face of increasing drought risk due to climate change in line with the aspirations of the universal sustainable development goals and the country's vision of attaining an upper middle-income society by 2030. A framework for creating drought resilience was developed to ensure that development stakeholders cooperate to build drought resilient communities in tropical regions with drought challenges like Zimbabwe and the rest of Southern Africa.